ANALISIS BRANDING KAFE CILOR MANTUL DALAM MENGOMUNIKASIKAN PRODUKNYA - Aryanti, Silpa; Bintang, Gilang (KOMUNIKA BANGSA, 2025)
This study analyzes the branding of Café Cilor Mantul in communicating its products amidst the competition of culinary MSMEs in Bunijaya Village. The success of Café Cilor Mantul in surviving and growing is the main reason, highlighting the importance of branding for business sustainability. The purpose of this study is to understand how Café Cilor Mantul's branding elements including the logo, brand name, Instagram visuals, and taglineare represented and communicated. The method of this research is descriptive qualitative with a constructivist paradigm, where data is collected through in-depth interviews with the owner and consumers and direct observation of the implemented branding elements. Branding theory is used as the basis for the analysis. The results of this study indicate that Café Cilor Mantul's logo successfully represents its main product through the use of specific icons, attractive colors, and clear typography, in accordance with the owner's objectives. The brand name "Cilor Mantul" proved effective in attracting attention due to its simplicity and local familiarity. Product visuals on Instagram also successfully attract interest through good photo/video quality, artistic composition, use of bright colors, and a focus on emotional experiences. Furthermore, the tagline "Makan Cepat Menu Tepat" represents service efficiency and menu diversity. Overall, the branding implementation of Kafe Cilor Mantul demonstrates success in building and communicating a strong brand identity through visual and verbal elements tailored to the product's characteristics and target market. This understanding is expected to contribute to Communication Studies in the field of branding and marketing, as well as serve as a practical reference for Kafe Cilor Mantul and other MSMEs in formulating effective brand strategies.